Young people's experience of family and schooling - Hudson, C; Hudson, Caroline (1999)
The thesis examines the extent to which 32 young people perceived that their family structure (intact nuclear, reordered nuclear, single-parent) influenced their experience of family and schooling. Through attempting to listen to the young people's voices on family, schooling and home-school issues, the thesis questions whether commonly used categories of family structure inform understanding of these young people's experience of family and schooling. The thesis is an ethnography, with a broadly symbolic interactionist framework, of one mixed ability tutor group in a large urban comprehensive school in central England. Fieldwork was conducted over two years, from September, 1996 to July, 1998. The main period of data collection was from November, 1996 to July, 1997, when the young people were in Year Nine. The main methods of data construction were interviews and informal conversations with the young people and observation of their experience of schooling. The literature review examines the large body of British quantitative research on outcomes (health, emotional and behavioural, and educational) according to family structure, and the much smaller corpus of British qualitative research focusing on the processes of family structure. It is highlighted that few British qualitative studies aim to access the voice of the child, focusing instead on adults' experience of family reordering or adults" perceptions of children's experience of reordering. The thesis examines the diversity in experience of family reordering of young people in reordered nuclear and single-parent families, the similarities in experience of reordering across these two categories of family structure, and the experience of family reordering of young people in intact nuclear families. The thesis assesses the extent to which family structure was important in the young people's relationships with the following family members: mothers, fathers (natural resident, natural non-resident and step), siblings (natural, step and half) and the extended family. The thesis develops a model for the young people's experience of family, Networks of Conflict: Networks of Support. The thesis examines the extent to which family structure, or other factors such as gender and school-related factors, were important in the young people's experience of the following aspects of schooling: friendship groups, behaviour, views on school, attainment and attendance. The thesis explores the extent to which family structure influenced parental involvement in their children's schooling and school intervention over homerelated issues. The extent to which the school's Health, Home and Community (HHC) curriculum tapped into the young people's expertise on family is examined. The thesis concludes that, overall, commonly used categories of family structure do little to inform understanding of the experience of family and schooling of these 32 young people; the boundaries around the categories of family structure are permeable.